Testing the Social Identity Model of Collective Action Longitudinally and Across Structurally Disadvantaged and Advantaged Groups - Thomas, Emma F.; Zubielevitch, Elena; Sibley, Chris G.; Osborne, Danny (Personality & social psychology bulletin, 2020)
Although the social identity model of collective action (SIMCA) demonstrates that identity, efficacy, and injustice are key correlates of collective action, longitudinal tests of these causal assumptions are absent from the literature. Moreover, most collective action research focuses on disadvantaged groups’ responses to injustice, with few studies examining what motivates advantaged groups to protest. We address these oversights using nationally representative longitudinal panel data to investigate SIMCA among members of disadvantaged (N = 2,574) and advantaged (N = 13,367) groups. As hypothesized, identity predicted increases in injustice, efficacy, and collective action support over time. In turn, injustice (but not efficacy) mediated the longitudinal association between identity and collective action support. Notably, results were largely consistent across disadvantaged and advantaged groups. Thus, we provide the first demonstration that identity temporally precedes collective action across objectively disadvantaged and advantaged groups, but identify complexities regarding the role of efficacy in protest.